Characterization of the Evolution with Temperature of the Structure and Properties of Geopolymer-Cordierite Composites - Franklin Casarrubios; Alexandre Marlier; Charlotte Lang; Sandra Abdelouhab; Isabella Mastroianni; Geoffroy Bister; Maurice-François Gonon (Ceramics)
This work is part of a research project aimed at producing ceramic-like materials, without the need for an initial sintering, for potential applications in catalysis or filtration at temperatures up to 1000 °C. In that context, cordierite-derived materials were prepared from recycled cordierite powder (automotive industry waste) bonded with metakaolin-potassium silicate geopolymer. The principle is that these materials, prepared at temperatures below 100 °C, acquire their final properties during the high-temperature commissioning. The focus is on the influence of the K/Al ratio and cordierite fraction on the stability of the dimensions and porosity during heating at 1000 °C, and on the final Young’s modulus and coefficient of thermal expansion. Conventional and high-temperature XRD evidenced the absence of crystallization of the geopolymer binder and interaction with the cordierite filler during the heating stage when K/Al = 1 or 0.75. By contrast, crystallization of kalsilite and leucite, and diffusion of potassium ions in the structure of cordierite is evidenced for K/Al = 1.5 and 2.3. These differences strongly influence the shrinkage due to sintering and the final properties. It is shown that a K/Al ratio of 0.75 or 1 is favorable to the stability of the porosity, around 25 to 30%. Moreover, a low coefficient of thermal expansion of 4 to 4.5 × 10−6 K−1 and a Young’s modulus of 40 to 45 GPa is obtained.